Radioactive ghosts - Schwab, Gabriele (University of Minnesota Press, 2020)
"Radioactive Ghosts hopefully conveys the need to see nuclearism as absolutely central to the debates about the anthropocene or capitalocene. Radioactive contamination is, after all, arguably the most destructive footprint humans have left on the planet. Within this larger framework, my focus on nuclear subjectivities also counters the current neglect of psychopolitics in political as well as ecological debates about nuclearism. Radioactive Ghosts presents steps toward a first comprehensive psychological theory of nuclear subjectivities with the hope to inspire further work in this direction."-- Preface.
Keywords: Nuclear warfare -- Philosophy.; Nuclear accidents -- Psychological aspects.; Radioactive pollution -- Philosophy.; Death -- Political aspects.; Psychic trauma -- Social aspects.; Nuclear energy -- Philosophy.; Nuclear weapons -- Philosophy.; Nuclear weapons -- Moral and ethical aspects.; Nuclear industry -- Moral and ethical aspects.; Nuclear waste -- Philosophy.; Guerre nucléaire -- Philosophie.; Accidents nucléaires -- Aspect psychologique.; Pollution radioactive -- Philosophie.; Mort -- Aspect politique.; Traumatisme psychique -- Aspect social.; Énergie nucléaire -- Philosophie.; Armes nucléaires -- Philosophie.; Armes nucléaires -- Aspect moral.; Industrie nucléaire -- Aspect moral.; HISTORY / Military / Nuclear Warfare; Death -- Political aspects; Nuclear energy -- Philosophy; Nuclear industry -- Moral and ethical aspects; Nuclear warfare -- Philosophy; Nuclear weapons -- Moral and ethical aspects; Psychic trauma -- Social aspects; nuclearism -- nuclear imaginary -- Haunting (Philosophy)